Factors influencing individual ability to follow physical distancing recommendations in Aotearoa New Zealand during the COVID-19 pandemic: a population survey. (31st May 2021) - Gray, Lesley; Rose, Sally B.; Stanley, James; Zhang, Jane; Tassell-Matamua, Natasha; Puloka, Viliami; Kvalsvig, Amanda; Wiles, Siouxsie; Murton, Samantha A.; Johnston, David M.; Becker, Julia S.; MacDonald, Carol; et al.
ABSTRACT: Physical distancing (also commonly known as social distancing) is an important non-pharmaceutical strategy to minimise the risk of transmission of SARS-CoV-2 virus. A range of restrictions to promote physical distancing form a key part of the Aotearoa New Zealand (NZ) all-of-government response to the global COVID-19 pandemic. The effectiveness of physical distancing strategies is highly dependent on buy-in and the actions of individuals, households and communities. This NZ population survey was conducted to identify people's views on the effectiveness of various strategies, and factors impacting on their capacity to follow physical distancing requirements during Alert Levels 4, 3, and 2 (April 24th–June 8th 2020). The majority of the 2407 participants were supportive of the public health measures implemented to promote physical distancing across Alert Levels. Few substantial differences were observed in relation to demographic characteristics, suggesting high overall levels of understanding and willingness to adhere to distancing requirements. Around half of the participants reported difficulties practicing physical distancing when in public. Reasons included being an essential worker and challenges related to the behaviour of others. These survey findings highlight the willingness of NZ's population to play their part in eliminating COVID-19 transmission, and the way in which behavioural change was rapidly adopted in line with government requirements.